Intercalation electrochemistry for thermoelectric energy harvesting from temperature fluctuations. Issue 8 (4th January 2022) - Heubner, Christian; Liebmann, Tobias; Schneider, Michael; Michaelis, Alexander
Abstract : A new concept of thermal energy harvesting is proposed that combines the advantages of thermo-electrochemical cells and pyroelectrics. Abstract : The effective use of energy from sustainable sources is considered a crucial step on the way to a CO2 -neutral economy. Low-grade waste heat (<100 °C) is widely and ubiquitously available, but difficult to convert into electrical energy with current technologies. Here, we demonstrate an electrochemical cell capable of directly converting ambient temperature fluctuations into electricity. Based on intercalation reactions with different entropies, any temperature change leads to a cell voltage and electrical energy can be extracted. The new cell concept features the advantages of thermo-electrochemical cells and pyroelectric-like energy harvesting, which opens a wide range of possibilities for effective and sustainable use of low-grade waste heat.